2018
DOI: 10.4103/jmh.jmh_59_17
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblastoma of the Breast: A Rare Cause of Breast Lump in a Postmenopausal Woman

Abstract: A breast mass in a postmenopausal age woman is treated with a high index of clinical suspicion for malignancy. Myofibroblastoma (MFB) of the breast is a very rare benign stromal tumor, predominantly occurring in menopausal women and older men. Owing to its rarity, nonspecific radiology, cytomorphology, and many variants, it can be confused with other malignant and benign breast lesions and hence can be a source of diagnostic pitfall. We present a case of an MFB of the breast in a 55-year-old female, which was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Myofibroblastoma is a rare, benign, stromal tumor of the mesenchyma with myofibroblastic differentiation [ 2 , 3 ]. It has been reported in mammary and extramammary regions [ 2 ], including the head, neck, soft tissue, skin, lymph node, axilla, parotid gland, and groin [ 4 - 7 ], with similar histology and immune‑phenotyping [ 1 ]. MFB was first described in 1987 by Wagortz et al, who reported 16 cases (11 in men) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Myofibroblastoma is a rare, benign, stromal tumor of the mesenchyma with myofibroblastic differentiation [ 2 , 3 ]. It has been reported in mammary and extramammary regions [ 2 ], including the head, neck, soft tissue, skin, lymph node, axilla, parotid gland, and groin [ 4 - 7 ], with similar histology and immune‑phenotyping [ 1 ]. MFB was first described in 1987 by Wagortz et al, who reported 16 cases (11 in men) [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the literature revealed 43 cases of MFB (25 men, 17 women, and one transgender patient aged 35-96 years). Among them, 24 were incidental findings on routine mammography screening [ 2 ] or other screenings for unrelated symptoms [ 1 , 12 ], and 19 involved a palpable mass or other symptoms [ 3 ]. Differential diagnoses for breast mass in males include gynecomastia, infection, lipoma, granular cell tumor, metastatic disease, and schwannoma [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MFB has been suggested to arise from mammary stromal fibroblasts with positivity for CD34 and vimentin markers. On the other hand, expression of ER, PR and AR receptors in these cells guided us to a probable role of sex steroid hormones in their pathogenesis (5). Myofibroblast cells are capable of multidirectional mesenchymal differentiation, which can further differentiate into smooth muscle, cartilage, or osseous tissue (1).…”
Section: Introductionmentioning
confidence: 99%